Signcryption with Non-interactive Non- repudiation without Random Oracles - Fan, Jia; Zheng, Yuliang; Tang, Xiaohu (Transactions on Computational Science X, 2010)
Non-repudiation is a very important requirement of signcryption. It ensures that a sender cannot deny the fact that he has signcrypted a message. Non-interactive non-repudiation enables a receiver to settle a repudiation dispute with the help of a judge without the need to engage in costly multi-round interactive communications with the judge. In this paper, we strengthen Malone-Lee’s security model for signcryption with non-interactive non-repudiation by introducing two additional, more subtle and useful security requirements, one about the unforgeability and the other about the confidentiality of non-repudiation evidence. A further contribution of this paper is to design a concrete signcryption scheme that admits provable security without random oracles in our strengthened security model for signcryption.